Posted by **fernando** on Sunday, July 15, 2007 at 6:26pm.

if x+ a= b/3x and b does not = 3 then x =?

i cant seem to find a way to seprate the two x's since 3/b is always attached.

subtract (b/3)x from both sides

x- (b/3) x+a=0

x(1-b/3)= -a

x= a/(1-b/3)

i looked at the back of my book and the answer is 3a/b-3

## Answer this Question

## Related Questions

- algebra equation solving - ((y+2)/(y^2-49))subtract ((y)/(y^2+6y-7)) subtract ...
- math - can anyone help me with these 3 problems I am trying to check my ...
- Math - 1. Write the expression as a function of an acute angle whose measure is ...
- math - the radius of a circle when the numeric values of the circumference and ...
- Algebra - How can I transform the equation 4=x-y into one that begins with "y...
- Algebra Repost - How can I transform the equation 4=x-y into one that begins ...
- Math - I have a problem..... -4(2x-3)=-8x+5 I understand first you distribute ...
- Algebra - Why are these algebraic expressions used and explain the logical error...
- ALgebra - Indicate and explain the logical error in the following set of ...
- MATH PLEASE CHECK IT!!2 - m-2/m-5*m+5/m-2=-1 If your problem is this: (m - 2)/(m...